Validation of SNPs Identified by Amplicon Sequencing and their Association with Egg Production and Egg Weight in Anand Synthetic White Leghorn and Anand Bantamised White Leghorn Chicken - Patel, Ayushi R.; Patel, Mayank R.; Golaviya, Akash G; Jhakesara, Subhash J; Patel, Ashish C; Koringa, Prakash G (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was aimed to validate the previously found SNPs using NGS-based amplicon sequencing and investigate of their association with egg production and egg weight by PCR-RFLP in Anand Synthetic White Leghorn (ASWLH) and Anand Bantamised White Leghorn (ABWLH) chicken. A total of 500 blood samples were collected including, 227 samples of ASWLH and 273 of ABWLH maintained at the Poultry Research Station, Anand Agricultural University, Anand, Gujarat. The study was conducted for a total of eight SNP markers located across the four genes involved in physiological pathways related to egg production and egg weight, viz., GnRHII (T88170424C), GnRHII (G88170427A), VIPR1 (C1826542A), VIPR1 (C1826555T), OCX32 (C21912308T), OCX32 (T21912084G), OCX32 (C21912423A) and GHR (C13415980T). Out of eight SNPs, C21912423A of the OCX32 gene was significantly associated with egg weight at the 40 weeks of age (EW40) in the whole population. The G88170427A of the GnRHII gene was significantly associated with egg weight at the 28 weeks of age (EW28) and C21912308T of the OCX-32 gene was significantly associated with total egg number at the age of 64 weeks (TWN64) in the whole population.
Keywords: Chicken; Egg Production; Egg Weight; PCR-RFLP; SNP validation; Real-Time PCR